Optimization of Digital Marketing in Increasing Sales BAKPIA Masaji Kediri UMKM Products - Yogi Dwi Lestari; Sudarmiatin (PT FORMOSA CENDEKIA GLOBAL, 2024)
In the current digital era, digital marketing has become a very important marketing strategy for the Micro, Small and Medium Enterprises (MSME) sector. The use of digital marketing can help MSMEs increase marketing reach, expand the customer base, and ultimately increase sales. This research aims to explore appropriate digital marketing strategies for Bakpia Masaji MSMEs in increasing sales and identifying challenges and opportunities in optimizing digital marketing. The data collection method used in-depth interviews with the owner of MSME Bakpia Masaji Kediri. The research results show that Bakpia Masaji has made maximum use of social media to promote its products, but still faces challenges in strengthening its brand image.